Urinalysis for the diagnosis of glomerulonephritis: role of dysmorphic red blood cells. Issue 8 (6th October 2017) - Hamadah, Abdurrahman M; Gharaibeh, Kamel; Mara, Kristin C; Thompson, Katherine A; Lieske, John C; Said, Samar; Nasr, Samih H; Leung, Nelson
Abstract: Background: Dysmorphic red blood cells (dRBCs) on urine microscopy have been associated with glomerulonephritis (GN). We assessed the prevalence and ability of dRBCs to differentiate GN from other kidney diseases. Methods: Adult patients with kidney biopsy performed between 2012 and 2015 at a single center who had a concurrent urinalysis were retrospectively studied. The association of ≥25% dRBCs with the presence of glomerular pathology was assessed. Univariate and multivariate logistic regression were performed on significantly associated variables. Results: The mean age of the 482 eligible subjects was 55 years and 47.7% were female. Overall, 173 (35.9%) had <25% and 76 (15.8%) had ≥25% urine dRBCs. Kidney biopsies revealed glomerular disease in 372 (77.2%) (GN 46% and non-GN 54%). At the dRBC threshold of ≥25% used at our center, a sensitivity of 20.4%, specificity of 96.3% and positive predictive value of 94.6% for glomerular disease were observed. In a logistic regression model, urine RBCs [>10 versus ≤10 (P < 0.001)] but not dRBCs ≥25% (P = 0.3) independently predicted the presence of GN. A scoring system (0–3) based on hematuria and proteinuria levels revealed the risk for biopsy-proven GN was 15% when the score was 0 compared with 83% when it was 3. Conclusions: The presence of ≥25% urine dRBCs is specific but not sensitive for GN. In this cohort, the combined hematuria (>10 RBCs/high-power field) and proteinuria performed just as well as dRBCs plus proteinuria to predict underlying GN. A model based on the degree of hematuria and proteinuria found on urinalysis was able to predict the presence of GN.